Organic livestock production in Slovenia - Kompan, Drago; Žgur, Silvester; Čepon, Marko (Acta Agraria Kaposváriensis, 2010)
Organic livestock production in Slovenia has oriented on milk and meat production with ruminants. Almost 90% of all agricultural area included in organic production belongs to livestock production on grassland. Slovenia has officially entered in the organic production close before year 2000. The trend of organic production from 2004 til 2009 is increasing, the most enlargement is on Equidae, Sheep, Pigs and Goat animals: 236, 199, 174 and 161% respectively. The organic surface present in Slovenia 6% of total used agricultural area.